A comprehensive dataset of therapeutic peptides on multi-function property and structure information - Baichuan Xiao; Yixiang Zhou; Long Zhao; Haodong Huang; Xuwen Fei; Yong-Biao Zhang (Scientific Data)
Abstract This paper presents a comprehensive dataset comprising 58,583 experimentally validated therapeutic peptides with annotated structure information. These peptides are grouped into 47 categories based on their function or therapeutic property like antimicrobial or glucose-regulatory, of which 21,130 are multi-function peptides and 54,722 possess structural annotation information. We believe this dataset can be useful for the relevant research of therapeutic peptides, especially for computational tool developments in therapeutic peptide discovery and further exploration of the ‘sequence-structure-function’ relationship for therapeutic peptides.